Analysis of Factors That Influence Delays in Submitting Financial Reports and Their Impact on Market Reactions: A Literature Review - Nisfiarani, Rizka Rifki; Prasteyo, Tri Joko; Suhendro, Saring (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
This research aims to analyze the influence of company size, profitability, leverage, and liquidity in influencing the timeliness of reporting and analyze market reactions to delays. The literature review method has used databases such as Sinta and Scopus for the last ten years. The research results show that company size can influence delays. The findings suggest that the relationship between firm size and delay is contextual. Good financial performance speeds up reporting, while leverage and solvency play a significant role. Delays hurt market reactions, triggering declines in stock prices and investor confidence. This research contributes to understanding factors that influence the timeliness of reporting, providing insight for management and investors for better decision-making.